Polynuclear gallium and indium aquacomplexes – supramolecular compounds with organic macrocyclic cavitand cucurbit[6]uril - Е. А. Mainicheva; О. А. Gerasko; V. P. Fedin (Тонкие химические технологии)
Polynuclear gallium and indium aquacomplexes were isolated as supramolecular compounds. Aquacomplexes and cucurbit[6]uril (СВ[6], C36H36N24O12) molecules are linked to each other through a system of hydrogen bonds between carbonyl groups of СВ[6] and aqua- or/and hydroxoligands of polycation